2016
DOI: 10.1155/2016/4561951
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Seeking Behavior of Persons with Acute Chagas Disease in Rural Argentina: A Qualitative View

Abstract: Chagas disease (CD) is a tropical parasitic disease largely underdiagnosed and mostly asymptomatic affecting marginalized rural populations. Argentina regularly reports acute cases of CD, mostly young individuals under 14 years old. There is a void of knowledge of health care seeking behavior in subjects experiencing a CD acute condition. Early treatment of the acute case is crucial to limit subsequent development of disease. The article explores how the health outcome of persons with acute CD may be condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
3
0
3
Order By: Relevance
“…Family doctors participating in our study also reported that in general, patients with CD could not relate the clinical manifestations to the disease, even though they knew the diagnosis. In Argentina the lack of information about CD also influenced the demand for care [ 46 ]. A study carried out in Spain pointed out that the low understanding of patients with CD in relation to the disease was not exclusively related to the patients' level of education, but also to the difficulties surrounding doctor-patient communication [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family doctors participating in our study also reported that in general, patients with CD could not relate the clinical manifestations to the disease, even though they knew the diagnosis. In Argentina the lack of information about CD also influenced the demand for care [ 46 ]. A study carried out in Spain pointed out that the low understanding of patients with CD in relation to the disease was not exclusively related to the patients' level of education, but also to the difficulties surrounding doctor-patient communication [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A highly sensitive automated method to screen for Chagas disease, such as the Elecsys Chagas assay, could potentially increase the throughput of samples and will likely lead to improvements in diagnosis algorithms and, thus, in cost-effectiveness ( 28 ). Ultimately, the availability of improved assays for the detection of T. cruzi would be expected to better safeguard patients who require blood and organ donation and help to minimize misdiagnoses, which are major factors in delaying the appropriate health care response ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of knowledge of clinical manifestations and a long indeterminate phase before possible progression might also hamper early treatment seeking behaviour [17,42,43] and has been described as a factor for underdiagnosis when infected individuals move to non-endemic cities or countries [17,[44][45][46]. Of great concern is the sparse awareness of treatment efficacy within newborn and children as well as in women of fertile age [38].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%